Lion-face faucets, Seth Samaldas Narsidas pyaav - Ghosh, Ayan (2023)
Seth Samaldas Narsidas pyaav has lion-faced faucets on four sides through which water emerges and flows into the stone trough at the bottom. The overspill is collected in the Koi Fish Pond and recycled through the fountain. The trough was added during restoration to suit the purpose of a fountain and a pyramidal capital was added at the top.